2012
DOI: 10.1007/s10103-012-1145-9
|View full text |Cite
|
Sign up to set email alerts
|

Laser skin rejuvenation: epidermal changes and collagen remodeling evaluated by in vivo confocal microscopy

Abstract: Fractionated carbon dioxide (CO2) laser resurfacing is an effective treatment of skin aging. Several studies investigated the morphologic changes due to this laser treatment by using skin biopsies or animal model. Recently, reflectance confocal microscopy (RCM) has emerged as a new tool that can "optically" scan the skin in vivo with a nearly histologic resolution and in a totally noninvasive modality. Our study aims to analyze the skin changes following the ablative fractional CO2 laser sessions by using RCM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 22 publications
4
75
0
3
Order By: Relevance
“…This collagen remodeling in the skin was present 3 months after the last laser session [40]. These data support the long-term effect of the treatment.…”
Section: Discussionsupporting
confidence: 57%
“…This collagen remodeling in the skin was present 3 months after the last laser session [40]. These data support the long-term effect of the treatment.…”
Section: Discussionsupporting
confidence: 57%
“…In a first clinical study published in 2009, Rahman et al 7 reported a marked improvement regarding rhytides, pigmentation, laxity and skin texture 3 months after one to two treatments. Longo et al 8 found intense collagen remodelling after fractional CO 2 laser resurfacing, which was still detectable 3 months after the treatment. Despite these promising findings, no objective data on wrinkle parameters before and after full-face treatment are currently available.…”
Section: Discussionmentioning
confidence: 98%
“…reported a marked improvement regarding rhytides, pigmentation, laxity and skin texture 3 months after one to two treatments. Longo et al . found intense collagen remodelling after fractional CO 2 laser resurfacing, which was still detectable 3 months after the treatment.…”
mentioning
confidence: 99%
“…52 Longo's histologic analysis of fractional ablative laser-treated skin noted persistent neocollagenesis 3 months posttreatment. 53 In addition to treating photoaging, fractional CO 2 lasers are also used to treat scars. In a study of 15 patients treated for moderate to severe acne scarring, 66.8% had an improvement after two or three full-face fractional CO 2 laser treatments.…”
Section: Nonablative Rejuvenationmentioning
confidence: 99%